Efektivitas E-Health Dalam Peningkatan Layanan Publik di Puskesmas Sawahan Kota Surabaya - Suhermawan, Divanda Erielya; Oktariyanda, Trenda Aktiva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation in public services has become a necessity in today’s era, including in the health sector, which demands fast, efficient, and easily accessible services for the public. Amid the rapid development of information technology, conventional health services are increasingly seen as inadequate in addressing the needs of modern society, particularly in terms of speed and equitable access. This situation highlights the need for technology-based innovations to improve the quality of public health services. One such innovation is the implementation of digital systems, such as the e-health application. The Surabaya City Government, through Puskesmas Sawahan, has implemented the e-health system to enhance the efficiency, quality, and accessibility of healthcare services for the community. However, its implementation still requires thorough evaluation to ensure that it truly meets public needs and aligns with the principles of e-government. This study aims to analyze the effectiveness of the e-health application in the context of public service delivery based on e-government. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observations, and document analysis. The theoretical framework refers to eight indicators of digital effectiveness proposed by Pedrosa et al. (2020): ease of use, usefulness, simplicity, trust, availability, comprehensibility, consistency, and service speed. The findings indicate that e-health generally improves administrative efficiency and broadens access to health services. However, several challenges remain, such as limited access to digital devices among the public, a lack of inclusive features for people with disabilities, and unclear data privacy policies. Based on these findings, the study recommends enhancing service features and ensuring transparency in data management as strategic steps toward a sustainable, equitable, and inclusive digital health service system.